Tele-audiology diagnostic testing services for children with disabilities in a school setting: A pilot study. (February 2023) - Ramkumar, Vidya; Krumm, Mark
Abstract: Objective: Children with disabilities (CWDs) having comorbidities face challenges in accessing and completing diagnostic hearing evaluations. This study was conducted to determine whether a tele-audiology diagnostic test battery can be administered to school-aged CWDs having comorbidities in a school-setting. Design: A proof-of-concept pilot study using a cross-sectional design. Study sample: Ten typically developing children between 3 years 9 months and 10 years 9 months of age; mean age of 8 years 3 months (pilot-norm group) and seven CWDs having comorbidities between 3 years and 8 years and 1 month of age; mean age of 5 years and 2 months (CWD group) participated in the study. A diagnostic test protocol delivered via tele-audiology was first administered to the pilot-norm group to ensure its efficiency and suitability for use in the CWD group. Following modifications, the diagnostic test protocol was delivered for CWDs. Results: We identified key aspects, including the role of the facilitator in conducting a diagnostic test battery using tele-audiology on CWDs, the usefulness of having co-facilitators to support child-friendly testing, as well as technology-related requirements. With respect to tele-audiology diagnostic testing, it was possible to quickly assess peripheral hearing using synchronous tele video-otoscopy, tympanometry, and DPOAEs. We identified limitations in conducting behavioral audiometry and completing tone-burst ABRs in CWDs. Conclusion: Evidence was obtained from this exploratory pilot study that a tele-audiology diagnostic test battery can be administered in a school setting to school-aged CWDs having comorbidities. Tele-audiology can be considered to provide hearing healthcare services to school-aged CWDs who may otherwise not receive these services.